2010
DOI: 10.1002/dvdy.22284
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of programmed cell fusion: Common mechanisms and distinct functions

Abstract: Eukaryotic cells have evolved diverged mechanisms to merge cells. Here, we discuss three types of cell fusion: (1) Non-self-fusion, cells with different genetic contents fuse to start a new organism and fusion between enveloped viruses and host cells; (2) Self-fusion, genetically identical cells fuse to form a multinucleated cell; and (3) Auto-fusion, a single cell fuses with itself by bringing specialized cell membrane domains into contact and transforming itself into a ring-shaped cell. This is a new type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 160 publications
0
19
0
Order By: Relevance
“…As a result of membrane contact, the outer phospholipid bilayers may provoke a transient fusion called hemifusion. Subsequently, the two membranes might locally form fusion pores or activation of fusogenic proteins leading to complete cell-cell fusion (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of membrane contact, the outer phospholipid bilayers may provoke a transient fusion called hemifusion. Subsequently, the two membranes might locally form fusion pores or activation of fusogenic proteins leading to complete cell-cell fusion (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches have a default assumption that MSCs 'learn' their phenotype from NPCs, and promote cell division in NPCs. However, the manner in which the NP phenotype can be mimicked by MSCs and whether or not this method is safe with regard to possible chromosomal rearrangement due to hybrid formation remain to be determined (22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to C. elegans, seamless tubules are also found in the Drosophila tracheal system (13,14), and endothelial cell capillaries in zebrafish (15,16) and mammalian tissues (17,18). While there are various mechanisms proposed for the formation of seamless capillaries in zebrafish (15,16), the mechanism underlying the formation of mammalian seamless capillaries remains unclear (19,20). Interestingly, we found that human microvascular endothelial cells were also capable of self-contact-induced membrane fusion (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…The fusion of mammalian cells into large syncytia is a well controlled process that is restricted to a limited set of cells, including gametes, macrophages, myoblasts, and trophoblasts [39,40]. Steinberg et al [38] demonstrated that the FGFRL1 receptor, when overexpressed, was capable of fusing CHO cells into multinucleated syncytia comprising several hundred nuclei.…”
Section: Biological Effects Of Fgfrl1mentioning
confidence: 99%